1984
DOI: 10.1007/bf01575247
|View full text |Cite
|
Sign up to set email alerts
|

A histopathological study of the percutaneous implantation of polyester fibers

Abstract: A histopathological study was made on scalp biopsies at 1 day, 1 week, 2 weeks, 1 month, 2 months, 5 months, and 20 months following implantation of synthetic fibers developed as artificial hair in Japan, in order to determine the histological conditions of its fixation over an extended period. In addition, the operative technique and materials for implantation were explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…22 Histologically at 12-18 months showed fiber surrounded by fibrosis and collagen. 23 No pigment was seen although the modifications vary depending on the anatomical structures in the path of the fiber, the inflammatory phenomena were extremely limited and did not produce clinically evident signs of inflammation. 17 Respect of correct patient selection, correct implant procedure, and proper after care is fundamental to avoid prospective problems.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…22 Histologically at 12-18 months showed fiber surrounded by fibrosis and collagen. 23 No pigment was seen although the modifications vary depending on the anatomical structures in the path of the fiber, the inflammatory phenomena were extremely limited and did not produce clinically evident signs of inflammation. 17 Respect of correct patient selection, correct implant procedure, and proper after care is fundamental to avoid prospective problems.…”
Section: Discussionmentioning
confidence: 98%
“…Inflammatory complications are described as mild reddening and itching 22 . Histologically at 12–18 months showed fiber surrounded by fibrosis and collagen 23 . No pigment was seen although the modifications vary depending on the anatomical structures in the path of the fiber, the inflammatory phenomena were extremely limited and did not produce clinically evident signs of inflammation 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of our study with the data reported by Hanke and Bergfeld 13 in 1981 on the fibers used in past is displayed in Table 3. Other reports also suggest better tolerance and fewer and less severe complications with newer artificial fibers 18–24 …”
Section: Commentsmentioning
confidence: 99%